Ordering Uncertain Prospects: The Multivariate Utility Functions Case - Russell, W. R.; Seo, T. K. (Review of Economic Studies, 1978)
William R. Russell, Tae Kun Seo; Ordering Uncertain Prospects: The Multivariate Utility Functions Case, The Review of Economic Studies, Volume 45, Issue 3,